Highly sensitive lateral flow immunoassays targeting PirA and PirB toxins for early on-site diagnosis of AHPND in shrimp - Chia-Chun Hsiao; You-Shan Cai; Shin-Yu Chou; Hung-Yun Lin; Shao-Chieh Yen; Han-Jia Lin; Shih-Chung Chang (Aquaculture, 2027)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Biochar-based cathodes for bioelectro-Fenton systems: Design strategies, electrocatalytic mechanisms, and environmental applications - Shu-Hui Liu; Chung-Yen Yeh; Wei-Tzu Huang; Yi-Chun Yu; Chi-Wen Lin (Journal of Environmental Chemical Engineering, 2026)

Nanoengineered Ce2CaMoO6 double perovskites derived oxide decorated on 2D P@g-C3N4 nanohybrid for the sensitive electrochemical sensing of antiscald agent diphenylamine in food and environmental matrices - Evangeline Jafneel Nixon; Abishek Jayapaul; Sanjay Ballur Prasanna; Chuan-Ming Tseng; Yu-Chien Lin; Da-Hua Wei; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Glucose-derived carbon-confined cu nanoparticles for selective nitrate reduction to ammonia under acidic conditions and biofouling-resistant wastewater treatment - Tsung-Ying Yang; Ko-Shan Ho; Kan-Yen Hsieh; Yu-Lin Hsiao; Sheng-Ci Jhong; Hsiu-Chung Tu (Journal of Water Process Engineering, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Beyond conventional biochar: Sulfur-iron modification unlocks redox control for synergistic cadmium-arsenic sequestration in paddy soils - Zihao Liang; Hua Lin; Honghu Zeng; Sze-Mun Lam; Jin-Chung Sin; Xuehong Zhang; Guo Yu; Mi Feng; Yanpeng Liang; Huawei Li; Yuxi Lu; Gongning Chen (Environmental Research, 2026)

Particle-Size Control of Radionuclide Enrichment and Environmental Risk Pathways in Slurry from the Wandan Mud Volcano - Chih-Chung Lin; Yu-Sheng Wang; Wei-Hsiang Huang; Ting-Chien Chen; Yuan-Fu Lu (Environmental Pollution, 2026)

Enhanced label-free SERS detection of uremic toxins in clinical spent dialysate - Han Lee; Jiunn-Der Liao; Yi-Shan Guo; Chung-Yu Wang; Kuan-Hung Liu; Szu-Hsueh Lai; Bo-Shen Lin (Analytica Chimica Acta, 2026)

End-to-end deep learning quadrature phase shift keying demodulation with channel and receiver impairments - Guan-Lin Liu; Chung-Yu Shih; Cissi Ying-tsen Lin (Advances in Space Research, 2026)

A coarse-to-fine machine-learning framework for identifying functional connectivity markers of cognitive impairment in Parkinson’s disease - Chung-Yao Chien; Tsung-Lin Lee; Tien-Yu Lin; Rwei-Ling Yu; Chou-Ching K. Lin (Medical & Biological Engineering & Computing, 2026)

Southern Asian arc magmatism drove Eocene global climate - Xiaoran Zhang; Shuiyue Xue; Sun-Lin Chung; Guochun Zhao; Yu-Ming Lai; Hao-Yang Lee; Ping-Ping Liu (Global and Planetary Change, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Lactate acts as a metabolic brake on inflammation by repressing NLRP3 transcription via NF-κB inhibition - Hsin-An Lin; Hsin-Chung Lin; Chih-Yung Chiou; Hao-Hsuan Peng; Yu-Jen Chen; Bo-Ying Bao; Kuen-Jou Tsai; Chao-Feng Lin; Chieh-Tien Shih; Sheng-I. Hu; Kuo-Yang Huang; Lih-Chyang Chen (Inflammation Research, 2026)

Synergistic transition binary metal oxide with multiwalled carbon nanotubes interfaces enabling sensitive electrochemical detection of preservative agent diphenylamine - Mosas Vinsy Arul Thomas; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Rajalakshmi Sakthivel; Ting-Yu Liu; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2026)

Enhancing environmental stress tolerance of Saccharomyces cerevisiae by deletion of NTH1 and FKS3: Implications for beer brewing - Chih-Yuan Tan; Huan-Yu Lin; Tsung-Tang Chen; Ying-Ta Shih; Yun-Chin Chung (International Journal of Food Microbiology, 2026)

Short-term exposure to nitrogen dioxide and risk of stroke-related re-admission: An analysis of the Taiwan National Health Insurance Research Database - Chen-Ting Yang; Yu-hsiang Lin; Hung-Lin Lin; Der-Cherng Chen; Chun-Chung Chen; Der-Yang Cho (Atmospheric Environment, 2026)

Purification, Identification, and Functional Validation of Anti-Inflammatory Peptides from Protein Hydrolysates of Asian Seabass, Lates Calcarifer by-Product - Hui-Chen Lin; Chung-Chih Tseng; Jia-Yu Lu; Hua-Yi Liang; Chun-Hung Liu (Marine Biotechnology, 2026)

Artificial intelligence and automated monitoring for Marine Protected Area Management: A case of Chaojing marine protected area in Taiwan - Yi-Chung Lee; Wen-Hong Liu; Yu-Shiuan Tsai; Li-Shu Chen; Dong-Lin Li (Ocean & Coastal Management, 2026)

Novel DUAL Z-SCHEME Bi2MoO6/SO3H@g-C3N4/ZnS photocatalyst enhanced by persulfate activation for rapid ofloxacin degradation: Integrated experimental and DFT studies - Imran Nasir Appau Zahir Hussain; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Introducing Double-Moment Warm Rain Physics into the Goddard 4ICE Microphysics Scheme - Kao-Shen Chung; Yu-Jyun Liou; Cheng-Rong You; Zhao-Cheng Zeng; Pay-Liam Lin; Donghai Wang; Wei-Kuo Tao; Stephen Lang; Takamichi Iguchi; Adrian Loftus; Jiun-Dar Chern (Asia-Pacific Journal of Atmospheric Sciences, 2026)
In this study, a new double-moment warm rain Goddard 4ICE scheme (GCEDM) is developed based on the Goddard 4ICE single-moment (GCESM) scheme and then tested using idealized 2D squall line and 3D supercell simulations. The addition of the total number concentrations for cloud water ( $$\:N_{TC}$$ ) and rainwater ( $$\:N_{TR}$$ ) enables this new scheme to simulate more diverse raindrop size distributions, making it more realistic. GCEDM has similar overall thermal and dynamic characteristics to GCESM but produces higher evaporation rates, predicted particle number concentrations, and mass mixing ratios than GCESM, leading to stronger cold pools than with GCESM. In addition, comparisons are made versus the Weather Research and Forecasting Model Double-Moment Microphysics 7-class scheme (WDM7), which was also improved from a single-moment 4-class ice scheme to a double-moment warm-rain scheme. WDM7 also shows a stronger cold pool, but the system characteristics and microphysical processes are quite different from the single-moment version of this scheme.

Reductant-driven structural evolution of zinc manganese oxide integrated beta-cyclodextrin for high-performance heavy metal detection - Monica Subramanian; Nandini Nataraj; I.-Hsuan Tung; Yu-Chien Lin; Cihun-Siyong Gong; Hsu-Wei Fang; Ren-Jei Chung (Process Safety and Environmental Protection, 2026)

Middle Eocene arc magmatism from Armenia with new insights into tectonic evolution of the Arabia-Eurasia collision zone - Yu-Chin Lin; Kwan-Nang Pang; Ghazar Galoyan; Rafael Melkonyan; Hao-Yang Lee; Ching-Hua Lo; Jin-Hui Yang; Sun-Lin Chung (Lithos, 2026)

Parylene-C templated synthesis of hierarchical bismuth nanoflowers for reversible chloride-ion storage - Sanjay Ballur Prasanna; Jian-Lin Lyu; Yu-Lin Lee; Ren-Jei Chung; Hong-ming Ku; Po-Chun Chen (Chemical Engineering Journal, 2026)

Methotrexate-loaded FeAuGd nanoparticles for synergistic magnetic-hyperthermia and chemotherapy - Kayalvizhi Samuvel Muthiah; Lenin Subramanian; Yen-Lin Chen; Udesh Dhawan; Yu-Chien Lin; Ching-Li Tseng; Ren-Jei Chung (Chemical Engineering Journal, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Protective effects of sodium benzoate against toluene-induced reward enhancement, behavioral disturbances, and impaired synaptic plasticity in mice - Chung-Pin Hsieh; Mei-Yi Lee; Chia-Yu Lin; Ming-Huan Chan; Hwei-Hsien Chen (NeuroToxicology, 2026)

Redox-active flower-like ZnMoO4 decorated on 2D graphene oxide nanohybrid as an efficient catalyst for sensitive electrochemical detection of a nitrofuran derivative in environmental and biological matrices - Amulya Garadi; Sanjay Ballur Prasanna; Po-Chun Chen; Gagankumar Sakleshpur Kumar; Nandini Nataraj; Yu-Chien Lin; Xinke Liu; Ting-Yu Liu; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Noise-resistant automatic seismic framework for monitoring rockslide slope - Chung-Ray Chu; Chiao-Yin Lu; Guan-Wei Lin; En-Jui Lee; Che-Hsin Liu; Chih-Hsin Chang; Hsiao-Yu Huang (Engineering Geology, 2026)

Aldehyde dehydrogenase 2 mitigates acrolein-driven ferroptosis to preserve kidney function - Yu-Ming Kuo; Shiu-Dong Chung; Jui-Ting Chang; Hui-Min Yang; Chieh-Chen Lee; Chih-Ching Lin; Hsiang-Tsui Wang (Environmental Pollution, 2026)

An accelerated meshfree computational framework with machine learning classification for multi-phase modeling of landslide - Kuan-Chung Lin; Yih-Chin Tai; Po-Han Lee; Hock-Kiet Wong; Yanran Wang; Yu-Shu Lu; Jiun-Shyan Chen (Computers and Geotechnics, 2026)

Phenol exposure promotes tumor-related signaling and blood vessel formation through the extracellular signal-regulated kinase/p38/hypoxia-inducible factor-1α pathway in cellular and zebrafish models - Chung-Yu Lin; Wangta Liu; Pei-Hsuan Chen; Chia C. Wang; Che-Hsin Lee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Additive-mediated controlled growth of printed perovskite for planar and heterostructure solar cells - Anjali Thakran; Yen-Yu Wang; Rohan Paste; Atul Dhage; Yu-Te Chen; Mario Hofmann; Yu-Jung Lu; Chung Hsin Lu; Shih- I. Lu; Yan-Duo Lin; Chih Wei Chu (Chemical Engineering Journal, 2026)

Cu2Te/Au@rGO aerogel as an efficient electrocatalyst for the bimodal electrochemical-colorimetric detection of 4-nitrotoluene - Nandini Nataraj; Agalya Mahalingam; Xinke Liu; Yu-Chien Lin; Ching-Wei Tung; Hsu-Wei Fang; Ren-Jei Chung (Process Safety and Environmental Protection, 2026)

Degradation of tetracycline by non-thermal plasma coupled with ferrocene-chitosan - Jingxuan Cao; Yuqing Huang; Shaohua Lin; Chung-Yu Guan; Haixia Wu (Journal of Water Process Engineering, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

Evaluating hygroscopic cloud-seeding effects by in-situ observation and real-case simulation - Kai-I Lin; Sheng-Hsiang Wang; Kao-Shen Chung; Pay-Liam Lin; Yu-Chieng Liou; Yi-Hui Chang; Yu-Chih Huang; Lin Yi-Sheng (Atmospheric Research, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Strategies for Promoting Sustainable Development of Land and Water Resources in a Land Subsidence Affected Area of Taiwan - Chung‐Feng Ding; Yu‐Ching Lin; Reuy‐Chi Kao (Irrigation and Drainage, 2025)
Land subsidence has been observed in many parts of the world. In Taiwan, the main cause is the excessive extraction of groundwater in alluvial plains. For limited land and water resources, it is essential to balance the development among economics, society and conservation issues in land subsidence‐affected areas. The Taiwan government promotes ‘prevention (non‐engineering)’ and ‘reclamation (engineering)’ strategies since the 1980s, which are to increase surface and alternative water supply, decrease groundwater abstraction, strengthen groundwater recharge, enhance enforcement related to water resources utilization and management, reduce induced disasters and encourage public participation. This paper reports the framework of prevention and reclamation strategies and their relative achievements; furthermore, it recently integrated ICT technology with low‐cost devices to monitor the regional pumping behaviour related to land subsidence for groundwater management. The real‐time monitoring system enables the utilization of groundwater more effectively and sustainably in reducing land subsidence. In 2022, according to the delimited goals of each strategy in every phase, all achievements were effective in mitigating the annual subsiding rate and affected area, the former from over 20 cm/year down to 8 cm/year, the latter from 1616 to 310 km 2 .

Outdoor-like running indoors: an enhanced adaptive treadmill with real-time physiological monitoring - Pei-Chun Hung; Yu-Chen Liu; Chun-Liang Lin; Wu-Chung Su; Chian-Yu Lu (Next Research, 2025)

Multifunctional visual photoelectrochemical sensor based on ternary Sb2WO6/P@g-C3N4/Ag2S nanocomposite for selective mercury-ion monitoring in environmental matrices and energy storage applications - Abishek Jayapaul; Sanjay Ballur Prasanna; Lu-Yin Lin; Rajalakshmi Sakthivel; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Physicochemical properties on the bone of hairtail (Trichiurus lepturus) under various treatments of cooking pressure and vinegar - Huey-Jine Chai; Shang-Ta Wang; Yun-En Chung; Yi-Ting Pan; Yu-Cheng Lin; Wen-Chieh Sung (International Journal of Gastronomy and Food Science, 2025)

Nanoengineered scheelite-structured SrWO4 decorated on MXene sheets: A novel platform for electrochemical sensing of the anti-cancer drug nilutamide with DFT insights - Akash Ashokrao Jagtap; Vaibhav Kanke; Rajalakshmi Sakthivel; Amar S. Katkar; Lu-Yin Lin; Yu-Chien Lin; Xinke Liu; Cihun-Siyong Gong; Ching-Wei Tung; Ren-Jei Chung (Environmental Research, 2025)

Simplified theoretical analyses of lagging Darcy flow and land subsidence in a groundwater pumping system of three horizontal layers: An elastic thin plate approach - Jun-Hong Lin; Chih-Yu Liu; Chien-Chung Ke; Ying-Fan Lin (Advances in Water Resources, 2025)

Mg-Fe isotopic constraint on the role of the lithosphere mantle in arc magmatism - Yang Yu; Xiao-Long Huang; Fan Yang; Yu Wang; Yi-Gang Xu; Iwan Setiawan; Sun-Lin Chung; Le Zhang; Guan-Hong Zhu (Lithos, 2025)

Injectable GelMA–PEDOT:PSS conductive hydrogel for cardiac-tissue engineering and integrated organic electrochemical transistor–based bioelectronic patch for biosensing and controlled extracellular vesicle release - Chung-Chuan Chou; Yu-Sheng Hsiao; Ming-Fu Hou; Pin-Yu Zhang; Min-Yu Hsieh; Lin-Yang Weng (Chemical Engineering Journal, 2025)

Description of Fulverythrobacter ferritrahens gen. nov., sp. nov., a Siderophore-Producing Bacterium Isolated from Poultry Manure Compost and Reclassification of Caenibius fulvus and Altererythrobacter segetis as Fulverythrobacter fulvus Comb. nov. and Croceibacterium segetis Comb. nov. - Shih-Yao Lin; Asif Hameed; Tzu-Yu Lin; Chiu-Chung Young (Current Microbiology, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

High-sensitivity Ara h1 detection with a praseodymium niobate-carbon nanofiber immunosensor - Evangeline Jafneel Nixon; Rajalakshmi Sakthivel; Yu-Chien Lin; Hsiao-Wei Wen; Ching-Wei Tung; Ren-Jei Chung (Food Chemistry, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Breaking charge transport barriers with synergistic redox dynamics in cobalt tellurium oxide-modified BiVO4: Experimental and DFT insights into enhanced photoelectrochemical water oxidation - Yu-Hsuan Chiu; Hamed Cheshideh; Akash Ashokrao Jagtap; Ren-Jei Chung; Lu-Yin Lin (Chemical Engineering Journal, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Specific locally, general globally: a synthesis on the isotopic niche in hammerhead sharks (Class Chondrichthyes, Genus Sphyrna) - Yu-Jia Lin; Hua-Hsun Hsu; Jen Chieh Shiao; Ming-Tsung Chung; Lotfi Jilani Rabaoui (Reviews in Fish Biology and Fisheries, 2025)

A numerical study of NO removal from exhaust gas at low-temperature using metal Zeolite catalysts - Way Lee Cheng; Ding-Hui Wang; Yi-Chi Chang; Pei-Cheng Cheng; Yu-Zheng Wang; Yuan-Chung Lin (Fuel, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Building with nature: Morphological spatial pattern of green infrastructure in urban heat mitigation - Bau-Show Lin; Yu-Hua Tsai; Han-Chin Chang; Chin-Chung Yu; Cheng-I Hsieh (Building and Environment, 2025)

Synergistic integration of dual Z-scheme Gd2Sn2O7/Ag3PO4/SnS2 heterojunction for accelerated visible-light photodegradation of sulfasalazine: Insights into DFT, toxicity, and antibacterial study - Akash Ashokrao Jagtap; Sanjay Ballur Prasanna; Susaritha Ramanathan; Sandeep Shadakshari; Kumara Swamy Ningappa; Yu-Chien Lin; Xinke Liu; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2025)

Bifunctional approach for electrochemical detection and catalytic degradation of Rhodamine B in environmental samples using a NiFe2O4@C/PPy catalyst: Kinetic and thermodynamic insights - Mosas Vinsy Arul Thomas; Sanjay Ballur Prasanna; Akash Ashokrao Jagtap; Gagankumar Sakleshpur Kumar; Yu-Chien Lin; Rajalakshmi Sakthivel; Ching-Wei Tung; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2025)

Rational engineering of dual Z-scheme Dy₂Sn₂O₇/MoS₂/Ag@g-C₃N₄ heterostructures for efficient tetracycline photodegradation via persulphate activation: Insights from DFT and experimental characterization - Akash Ashokrao Jagtap; Dhanashri D. Khandagale; Susaritha Ramanathan; Sanjay Ballur Prasanna; Yu-Chien Lin; Norman Lu; Sea-Fue Wang; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2025)

Predicting and regulating potential zone for heavy metal re-contaminated farmland: Case study in Taiwan - Jieh-Haur Chen; Mu-Chun Su; Meng-Fen Yeh; Wei-Jen Lin; Tzuyang Yu; Ming-Chung Yeh (Environmental Development, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Origin and metamorphism of ophiolitic serpentinites from the Yuli belt, eastern Taiwan: new findings and tectonic implications - Dominikus Deka Dewangga; Chin-Ho Tsai; Yoshiyuki Iizuka; Ilona Talvikki Sakaguchi; Yui Kouketsu; Sun-Lin Chung; Chi-Yu Lee; Wen-Yen Chang; Huei-Fen Chen (International Geology Review, 2025)

Enhancing the Fe3+/Fe2+ biocatalytic cycle using deoxidizing and iron-releasing sticks to improve bio-fenton efficiency - Chi-Wen Lin; Chung-Yen Yeh; Chih-Yu Ma; Shu-Hui Liu (Journal of Water Process Engineering, 2025)

Enhanced electrocatalytic conversion of CO2 to CO via a non-stoichiometric zinc-fluorine amorphous interface - Hsin-Chiao Wu; Chia-Chen Lin; Chu-Hsin Yang; Yu-Wei Huang; Chen-Hao Yeh; Yu-Jen Chou; Ta-Chung Liu (Chemical Engineering Journal, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Interpretation of machine learning-based prediction models and functional metagenomic approach to identify critical genes in HBCD degradation - Yu-Jie Lin; Ping-Heng Hsieh; Chun-Chia Mao; Yang-Hsin Shih; Shu-Hwa Chen; Chung-Yen Lin (Journal of Hazardous Materials, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Photo-responsive g-C3N4/copper molybdate nanocomposites enable laser-driven multi-modal imaging, photothermal and chemodynamic therapy for hepatocellular carcinoma treatment - Kayalvizhi Samuvel Muthiah; Sathan Raj Natarajan; Selvaraj Jayaraman; Udesh Dhawan; Yu-Chien Lin; Ren-Jei Chung (Chemical Engineering Journal, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

AI integration into wavelength-based SPR biosensing: Advancements in spectroscopic analysis and detection - Ying-Feng Chang; Yu-Chung Wang; Tsung-Yu Huang; Meng-Chi Li; Sin-You Chen; Yu-Xen Lin; Li-Chen Su; Kwei-Jay Lin (Analytica Chimica Acta, 2025)

New age and geochemical constraints on the “Old Andesite” and Middle Miocene adakites from Pacitan, East Java, Indonesia - Lediyantje Lintjewas; Yu-Ming Lai; Iwan Setiawan; Sun-Lin Chung; Andrie Al Kautsar; Hao-Yang Lee; Long Xiang Quek; Yoshiyuki Iizuka (Lithos, 2025)

High performance catalyst CoNP for efficient electrochemical production of hydrogen peroxide - Ko-Shan Ho; Kuan-Ying Hung; Yu-Lin Hsiao; Hsiu-Chung Tu (Journal of Environmental Chemical Engineering, 2025)

Economic viability and overall performance analysis of optimized Cu-Fe-ZSM-5 catalyst for NOx and particulate matter removal using NH3-SCR - Shivani Shirke; Feng-Chih Chou; Yu-Zheng Wang; Yuan-Chung Lin (Fuel, 2025)

Accelerated photocatalytic degradation of furaltadone antibiotic over a dual Z-scheme Er2Sn2O7/NiS2/V@g-C3N4 heterostructure by persulfate under visible-light irradiation: DFT, toxicity, and antibacterial activity studies - Sanjay Ballur Prasanna; Akash Ashokrao Jagtap; Susaritha Ramanathan; Lu-Yin Lin; Yeh-Fang Duann; Gagankumar Sakaleshpur Kumar; Hema Mylnahalli Krishnegowda; Yu-Chien Lin; Ren-Jei Chung (Chemical Engineering Journal, 2025)

Determinants of soundscape quality of communal open space in Hong Kong - Minqi LIN; Chi Kwan CHAU; Shiu Keung TANG; Wai Kit CHUNG; Ho Man YU (Building and Environment, 2025)

ω-9 monounsaturated fatty acids in Sapindus mukorossi seed oil enhance calcium deposition expression of Wharton’s jelly mesenchymal stem cells - Yu-Xuan Huang; Yen-Chung Lin; Chin-Kai Lin; Haw-Ming Huang (Tissue and Cell, 2024)

Synergistic low-temperature plasma degradation of tetracycline with ferrocene - Wang Shen; Haixia Wu; Zhonghong Tan; Shaohua Lin; Chung-Yu Guan (Journal of Environmental Management, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Effects of physical sterilization on microbial safety, nutritional composition, and antioxidant activity of queen bee larva powder, a by-product of royal jelly production - Yu-Hsin Chen; Jer-An Lin; Chi-Chung Peng; Pei-Shou Hsu; Tzu-Hsien Wu; Yen-Hou Chen; Ming-Cheng Wu (Food Control, 2024)

Selective and stable visible-light-prompted scavenger-free photoelectrochemical strategy based on a ternary ErVO4/P@g-C3N4/SnS2 nanocomposite for the detection of lead ions in different water samples - Abishek Jayapaul; Sanjay Ballur Prasanna; Lu-Yin Lin; Yeh-Fang Duann; Yu-Chien Lin; Ren-Jei Chung (Environmental Pollution, 2024)

High-contrast electrochromic coatings and devices for health assurance, visual comfort and energy-saving in buildings - Chung-Wen Kuo; Han-Yu Chen; Chen-Hao Yeh; Yuan-Chung Lin; Jeng-Kuei Chang; Pei-Ying Lee; Tzi-Yi Wu (Energy and Buildings, 2024)

Visible-light-prompted photoelectrochemical sensors fabricated using Er3NbO7/P@g-C3N4/SnS2 nanocomposite for detecting mercury ion in environmental water samples - Abishek Jayapaul; Yu-Chien Lin; Ying-Chu Chen; Ting-Yu Liu; Ren-Jei Chung (Chemosphere, 2024)

Cellulose acetate-coated capacitive sensor for determining carbon-cycle enzymes activity and as a microbial Indicator for soil health - Chung-Ting Cheng; Yu-Lin Wu; Yung-Te Hou; Tzong-Jih Cheng (Science of The Total Environment, 2024)

Geochemical characteristics of peridotite xenoliths from the Vitim volcanic field: Insight to late Cenozoic mantle upwelling in SE Siberia - Yu-Hsiang Chien; Kuo-Lung Wang; Victor Kovach; Mikhail Kuzmin; Alexender Vorontsov; Alexei Ivanov; Kwan-Nang Pang; Yoshiyuki Iizuka; Hao-Yang Lee; Sun-Lin Chung; Der-Chuen Lee (Lithos, 2024)

Facile synthesis of tantalum decorated on iron selenide with nitrogen-doped graphene hybrid for the sensitive detection of trolox in berries: Density functional theory interpretation - Rajalakshmi Sakthivel; Chun-Chien Chou; Sanjay Ballur Prasanna; Hema Mylnahalli Krishnegowda; Sayee Kannan Ramaraj; Lu-Yin Lin; Xinke Liu; Yu-Chun Lu; Hsiao-Wei Wen; Ting-Yu Liu; Ren-Jei Chung (Food Chemistry, 2024)

Description of Aliirhizobium terrae sp. nov., A Plant Growth-Promoting Bacterium Isolated from a Maize-Rice Rotation Agriculture Field - Shih-Yao Lin; Tzu-Yu Lin; Asif Hameed; Chia-Fang Tsai; Chiu-Chung Young (Current Microbiology, 2024)

2D sheet structure of zinc molybdate decorated on MXene for highly selective and sensitive electrochemical detection of the arsenic drug Roxarsone in water samples - Nareshkumar Baskaran; Sanjay Ballur Prasanna; Kanimozhi Jeyaram; Yu-Chien Lin; Mani Govindasamy; Yang Wei; Ren-Jei Chung (Chemosphere, 2024)

Elevated surface ozone concentration caused by subtropical cyclones and topographical effect: Model simulation and field measurement - Kuo-Cheng Lo; Wen-Hsi Cheng; Chitsan Lin; Chung-Hsuang Hung; Chung-Shin Yuan; Yu-Lun Tseng (Urban Climate, 2024)

Dual Z-scheme heterojunction Ce2Sn2O7/Ag3PO4/V@g-C3N4 for increased photocatalytic degradation of the food additive tartrazine, in the presence of persulfate: Kinetics, toxicity, and density functional theory studies - Sanjay Ballur Prasanna; Gagankumar Sakleshpur Kumar; Rajalakshmi Sakthivel; Karthik Chimatahalli Shanthakumar; Lu-Yin Lin; Yeh-Fang Duann; Yu-Chien Lin; Yu-Chun Lu; Ren-Jei Chung (Environmental Pollution, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

The different adsorption-degradation behaviors of SARS-CoV-2 by bioactive chemicals in wastewater: The suppression kinetics and their implications for wastewater-based epidemiology - Mohamed Bayati; Hsin-Yeh Hsieh; Shu-Yu Hsu; Sally Qasim; Chenhui Li; Anthony Belenchia; Jessica Klutts; Sally A. Zemmer; Kristen Sibley; Melissa Reynolds; Elizabeth Semkiw; Hwei-Yiing Johnson; et al. (Science of The Total Environment, 2024)

Mild chemical recycling of carbon fiber-reinforced epoxy composites in aqueous buffers and development of hydrothermally recyclable vitrimer composites from recyclates - Cheng Hao; Baoming Zhao; Lin Shao; Yiding Cao; Mingen Fei; Wangcheng Liu; Tuan Liu; Yu-Chung Chang; Kevin L. Simmons; Jinwen Zhang (Resources, Conservation and Recycling, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Design of a pebbles-like erbium stannate integrated with graphene nanoribbons for the anti-cancer drug nilutamide detection in water and biological samples - Abishek Jayapaul; Rajesh Kumar Panda; Sayee Kannan Ramaraj; Lu-Yin Lin; Yeh-Fang Duann; Yu-Chien Lin; Yu-Chun Lu; Wai-Ching Liu; Ching-Wei Tung; Rajalakshmi Sakthivel; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

A Ce2MgMoO6 double perovskite decorated on a functionalized carbon nanofiber nanocomposite for quantification of ciprofloxacin in milk and honey samples: Density functional theory interpretation - Akash Ashokrao Jagtap; Sanjay Ballur Prasanna; Gagankumar Sakaleshpur Kumar; Yu-Chien Lin; Udesh Dhawan; Yu-Chun Lu; Rajalakshmi Sakthivel; Ching-Wei Tung; Ren-Jei Chung (Chemosphere, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

Enzymatic impregnation by high hydrostatic pressure for preparing shape-retaining softened broccoli and carrot - Yu-Hsiang Wu; Bo-Chi Huang; Yan-Han Lin; Chung-Yi Wang (Food Bioscience, 2024)

Unleashing the potential of waste: A supercharged high-performance 3D printing resin from discarded polylactic acid - Yu-Chung Chang; Lin Shao; Wangcheng Liu; Brian J. Bliss; Baoming Zhao; Zihui Zhao; Jinwen Zhang (Chemical Engineering Journal, 2024)

Columnar aerosol types and compositions over peninsular Southeast Asia based on long-term AERONET data - Sheng-Hsiang Wang; Hsiang-Yu Huang; Che-Hsuan Lin; Shantanu Kumar Pani; Neng-Huei Lin; Chung-Te Lee; Serm Janjai; Brent N. Holben; Somporn Chantara (Air Quality, Atmosphere & Health, 2024)
Aerosol chemical components such as black carbon (BC) and brown carbon (BrC) regulate aerosol optical properties, which in turn drive the atmospheric radiative forcing estimations due to aerosols. In this study, we used the long-term measurements from AERONET (Aerosol Robotic Network) to better understand the aerosol types and composition with respect to their seasonal and spatial variabilities in peninsular Southeast Asia (PSEA, here defined as Vietnam, Cambodia, Thailand, Laos, and Myanmar). Two methods (i.e., aerosol type cluster and aerosol component retrieval) were applied to determine the aerosol type and chemical composition during the biomass-burning (BB) season. AERONET sites in northern PSEA showed a higher AOD (aerosol optical depth) compared to that of southern PSEA. Differences in land use pattern, geographic location, and weather regime caused much of the aerosol variability over PSEA. Lower single-scattering albedo (SSA) and higher fine-mode fraction (FMF) values were observed in February and March, suggesting the predominance of BB type aerosols with finer and stronger absorbing particles during the dry season. However, we also found that the peak BB month (i.e., March) in northern PSEA may not coincide with the lowest SSA once dust particles have mixed with the other aerosols. Furthermore, we investigated two severe BB events in March of 2014 and 2015, revealing a significant BrC fraction during BB event days. On high AOD days, although the BC fraction was high, the BrC fraction remained low due to lack of aerosol aging. This study highlights the dominance of carbonaceous aerosols in the PSEA atmosphere during the BB season, while also revealing that transported dust particles and BrC aerosol aging may introduce uncertainties into the aerosol radiative forcing calculation.

Synergistic activation of lamellar bismuth selenide anchored functionalized carbon nanofiber for detecting hazardous carbendazim in environmental water samples - Abishek Jayapaul; Yu-Chien Lin; Lu-Yin Lin; Udesh Dhawan; Yeh-Fang Duann; Yi-Hsuan Lee; Ting-Yu Liu; Rajalakshmi Sakthivel; Ren-Jei Chung (Chemosphere, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Multi-functional hydrogen- and oxygen-capturing FeCo-N-C catalyst with improved hydrogenation of nitroarenes and ORR activity - Hsiu-Chung Tu; Yu-Lin Hsiao; Yi-Dong Lin; Yan-Gu Lin; Ding-Liang Liao; Ko-Shan Ho (Chemical Engineering Journal, 2024)

Backward and forward simulation of polycyclic aromatic hydrocarbons by the grid-scale model _validation and applications for environmental management - Ming-Tsuen Hsieh; Wen-Yu Chung; Shoiw-Mei Tseng; Pei-Chi Shih; Shau-Ku Huang; Chon-Lin Lee (Atmospheric Environment, 2024)

Extinction coefficient of dry and deliquescent chemical components of PM_(2.) 5 in urban areas and their impacts on visibility deterioration - Chien-Hao Lin; Shao-En Sun; Chung-Te Lee; Ting-Yu Chiang; Shih-Yu Chang; Tzu-Shuan Wu; Hsin-Yu Wei; Ling-Ya Chen; Hao-Wei Liu; Sally C.W. Tai (Atmospheric Pollution Research, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Self-synthesis and performance analysis of a Cu-Fe composite ZSM-5 zeolitic catalyst for NOx reduction and particulate matter removal using NH3 SCR - Shivani Shirke; Feng-Chih Chou; Yu-Zheng Wang; Pei-Cheng Cheng; Shang-Cyuan Chen; Yuan-Chung Lin (Journal of Environmental Chemical Engineering, 2024)

Impacts of ship emissions and sea-land breeze on urban air quality using chemical characterization, source contribution and dispersion model simulation of PM2.5 at Asian seaport - Yu-Lun Tseng; Wen-Hsi Cheng; Chung-Shin Yuan; Kuo-Cheng Lo; Chitsan Lin; Chia-Wei Lee; Gerry Bagtasa (Environmental Pollution, 2024)

Simultaneous electrochemical and colorimetric detection of tri-heavy metal ions in environmental water samples employing 3D-MOF/nickel selenide as a synergistic catalyst - Nandini Nataraj; Pranjyan Dash; Rajalakshmi Sakthivel; Yu-Chien Lin; Hsu-Wei Fang; Ren-Jei Chung (Chemical Engineering Journal, 2024)

Streptococcus taonis sp. nov., a novel bacterial species isolated from a blood culture of a patient - Chien-Yu Lee; Chin-Kan Chan; Momoko Chida; Mika Miyashita; Yun-Shien Lee; Hui-Chung Wu; Yu-Chung Chang; Wen-Ting Lin; Yi-Sheng Chen (Archives of Microbiology, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

The two-back task leads to activity in the left dorsolateral prefrontal cortex in schizophrenia patients with predominant negative symptoms: a fNIRS study and its implication for tDCS - Chin-Chao Ma; Yen-Yue Lin; Yong-An Chung; Sonya Youngju Park; Cathy Chia-Yu Huang; Wei-Chou Chang; Hsin-An Chang (Experimental Brain Research, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Overdose with the anesthetic propofol causes hematological cytotoxicity and immune cell alteration in an experimental ex vivo whole blood culture model - Chung-Hsi Hsing; Yu-Ping Hung; Ming-Chung Lin; Chia-Ling Chen; Yung-Ting Wang; Po-Chun Tseng; Rahmat Dani Satria; Chiou-Feng Lin (Toxicology in Vitro, 2024)

Spatiotemporal variation and inter-transport of atmospheric speciated mercury between Kaohsiung Harbor and neighboring urban areas - I-Chieh Tu; Chung-Shin Yuan; Yu-Lun Tseng; Chia-Wei Lee; Chitsan Lin (Environmental Pollution, 2024)

Exploring the potential of the nano-based sunscreens and antioxidants for preventing and treating skin photoaging - Chih-Hung Lin; Ming-Hsien Lin; Yu-Kuo Chung; Ahmed Alalaiwe; Chi-Feng Hung; Jia-You Fang (Chemosphere, 2024)

Impact of heat on emergency hospital admissions related to kidney diseases in Texas: Uncovering racial disparities - Chunyu Guo; Erjia Ge; Manzhu Yu; Changwei Li; Xiangqian Lao; Shuang Li; Jason Glaser; Yongqun He; Marina Almeida-Silva; Sisi Meng; Wei-Chung Su; Junfeng Zhang; et al. (Science of The Total Environment, 2024)

2D/2D heterostructure Ni-Fe LDH/black phosphorus nanosheets with AuNP for noxious substance diphenylamine detection in food samples - Sanjay Ballur Prasanna; Yu-Chien Lin; Sayee Kannan Ramaraj; Udesh Dhawan; Xinke Liu; Ching-Wei Tung; Rajalakshmi Sakthivel; Ren-Jei Chung (Food Chemistry, 2024)

Dual Z-scheme Pr2Sn2O7/P@g-C3N4/SnS2 heterojunctions for the removal of tetracycline antibiotic by persulfate activation: Kinetics, thermodynamic parameters, density functional theory, and toxicity studies - Sanjay Ballur Prasanna; Rajalakshmi Sakthivel; Karthik Chimatahalli Shanthakumar; Santhosh Arehalli Shivamurthy; Yu-Chien Lin; Udesh Dhawan; Xinke Liu; Ren-Jei Chung (Chemical Engineering Journal, 2024)

Exposure to phenols reduces melanogenesis in B16F10 cells and zebrafish - Chung-Yu Lin; Chang-Yi Wu; Chia C. Wang; Che-Hsin Lee (Aquatic Toxicology, 2024)

Genetic diversity and relatedness of feline parvovirus in Vietnam and its potential implications for canine-feline transmission - Hoang Minh; Nguyen Vu Son; Hoang Minh Duc; Chao-Nan Lin; Yu-Chung Tyan; Kuo-Pin Chuang (Archives of Virology, 2024)

Comparison of high-hydrostatic pressure and frozen treatments on raw freshwater clam marinated in soy sauce: Impact on microbiological and organoleptic qualities - Pi-Chen Wei; Yi-Chen Lee; Yu-Chi Chen; Chung-Saint Lin; Po-Wei Chen; Todd Hsu; Yung-Hsiang Tsai (Food Control, 2023)

Side chain modulated carbazole-based bifunctional hole-shuttle interlayer simultaneously improves interfacial energy level alignment and defect passivation in high-efficiency perovskite solar cells - Yuan-Yu Chiu; Shih-Hsuan Chen; Kun-Mu Lee; Tz-Feng Lin; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

IoT-interfaced solid-contact ion-selective electrodes for cyber-monitoring of element- specific nutrient information in hydroponics - Yi-Min Wu; Shao-Yuan Liu; Bo-You Shi; Jui-Yu Peng; Zhi-Wei Kao; Yi-Yi Chen; Ting-Yu Hsieh; Hsing-Ying Chung; Chi-Yi Lin; Wei Fang; Lin-Chi Chen (Computers and Electronics in Agriculture, 2023)

Highly responsive and sensitive non-enzymatic electrochemical sensor for the detection of β-NADH in food, environmental and biological samples using AuNP on polydopamine/titanium carbide composite - Sanjay Ballur Prasanna; Aboud Ahmed Awadh Bahajjaj; Yi-Hsuan Lee; Yu-Chien Lin; Udesh Dhawan; Rajalakshmi Sakthivel; Ren-Jei Chung (Food Chemistry, 2023)

Association between glyphosate exposure and cognitive function, depression, and neurological diseases in a representative sample of US adults: NHANES 2013–2014 analysis - Ching Chung Hsiao; An-Ming Yang; ChiKang Wang; Chien-Yu Lin (Environmental Research, 2023)

Rapid identification and monitoring of cooking oil fume-based toxic volatile organic aldehydes in lung tissue for predicting exposure level and cancer risks - Karthikeyan Prakasham; Swapnil Gurrani; Chia-Fang Wu; Ming-Tsang Wu; Tusty-Jiuan Hsieh; Chiung-Yu Peng; Po-Chin Huang; Anbarasu Krishnan; Pei-Chien Tsai; Yu-Chia Lin; Bongee Tsai; Yuan-Chung Lin; et al. (Chemosphere, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Valorization of heavy metal-adsorbed microalgae from a membrane bioreactor for levulinic acid production - Chung-Yu Guan; Yen-Lin Kao; Van Toi Pham; Pei-Hsun Wu; Chang-Ping Yu (Journal of Environmental Chemical Engineering, 2023)

Different B Mo isotopic fractionation processes controlled by redox conditions in the subduction zone - Yang Yu; Xiao-Long Huang; Yu-Ming Lai; Jie Li; Yi-Gang Xu; Sun-Lin Chung; Iwan Setiawan; Fan Yang (Chemical Geology, 2023)

Temporal transition trends of cord blood lead levels in various human development index countries and in the Taipei metropolitan area - Yaw-Huei Hwang; Hui-Chu Wu; Ming-Kwang Shyu; Chien-Nan Lee; Shin-Yu Lin; Pau-Chung Chen; Hung-Yi Chuang; Pei-Wen Lin; Tso-Hsien Wu; Yen-Tzu Chen (Environmental Pollution, 2023)

Toward ultra-high efficiency tandem OLEDs: Benzothiazole-based bipolar hosts and specific device architectures - Jui-Ming Wang; Ting-Chun Lee; Chia-Chen Chung; Wun-Yu Chen; Sih-Yu Wu; Yan-Ding Lin; Yuan Jay Chang; Chin-Wei Lu; Chih-Hao Chang (Chemical Engineering Journal, 2023)

Perceptions of Taiwanese owners and behaviour veterinarians on behavioural problems in dogs and preferred training approaches - Hao-Yu Shih; Yu-Min Chang; Kris Descovich; Wen-You Liang; Chung-Hsi Chou; Yi-Chun Lin (Applied Animal Behaviour Science, 2023)

Edge-based wireless imaging system for continuous monitoring of insect pests in a remote outdoor mango orchard - Dan Jeric Arcega Rustia; Wei-Che Lee; Chen-Yi Lu; Ya-Fang Wu; Pei-Yu Shih; Sheng-Kuan Chen; Jui-Yung Chung; Ta-Te Lin (Computers and Electronics in Agriculture, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

Air quality health index (AQHI) based on multiple air pollutants and mortality risks in Taiwan: Construction and validation - Mu-Jean Chen; Yue Leon Guo; Pinpin Lin; Hung-Che Chiang; Pau-Chung Chen; Yu-Cheng Chen (Environmental Research, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Bona fide upcycling strategy of anhydride cured epoxy and reutilization of decomposed dual monomers into multipurpose applications - Lin Shao; Yu-Chung Chang; Baoming Zhao; Xinyan Yan; Brian J. Bliss; Ming-en Fei; Chenhao Yu; Jinwen Zhang (Chemical Engineering Journal, 2023)

Chemical fingerprints and source resolution of atmospheric fine particles in an industrial harbor based on one-year intermittent field sampling data - Yu-Lun Tseng; Chung-Shin Yuan; Kwok-Wai Wong; Chitsan Lin (Science of The Total Environment, 2023)

Evaluation of a subtropical maize-rice rotation system maintained under long-term fertilizer inputs for sustainable intensification of agriculture - Asif Hameed; Yu-Pei Chen; Fo-Ting Shen; Shih-Yao Lin; Hsin-I Huang; Yu-Wen Lin; Chiu-Chung Young (Applied Soil Ecology, 2023)

A rapid, high-throughput, and sensitive PEG-precipitation method for SARS-CoV-2 wastewater surveillance - Xiawan Zheng; Mengying Wang; Yu Deng; Xiaoqing Xu; Danxi Lin; Yulin Zhang; Shuxian Li; Jiahui Ding; Xianghui Shi; Chung In Yau; Leo L.M. Poon; Tong Zhang (Water Research, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Microbiome reengineering by four environmental factors for the rapid biodegradation of trichloroethylene - Yu-Hsuan Cheng; Shu-Chi Chang; Yan-Lin Lai; Chung-Chi Hu (Journal of Environmental Management, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Lightweight Flexible Polyimide-Derived Laser-Induced Graphenes for High-Performance Thermal Management Applications - Yu-Sheng Hsiao; Cai-Wan Chang-Jian; Tzu-Yen Huang; Ying-Lin Chen; Chung-Wei Huang; Jen-Hsien Huang; Nian-Jheng Wu; Shih-Chieh Hsu; Chih-Ping Chen (Chemical Engineering Journal, 2023)

Hydroxychloroquine repairs burn damage through the Wnt/β-catenin pathway - Sheau-Chung Tang; Chun-Te Lu; Jiunn-Liang Ko; Cheng-Hui Lin; Yu-Ping Hsiao (Chemico-Biological Interactions, 2023)

Gas-phase and PM2.5-bound phthalates in nail salons: characteristics, exposure via inhalation, and influencing factors - Chia-Ling Chang; Hui-Tzu Chen; Chung-Yu Chen; En-Yu Chen; Kuan-Ting Lin; Chien-Cheng Jung (Environmental Science and Pollution Research, 2023)

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

Activity concentrations and bioconcentration factors (BCFs) of natural radionuclides (40 K, 226Ra, and 232Th) from cultivated substrates to mushrooms - Wei-Hsiang Huang; Chih-Chung Lin; Yung-Yu Liu; Chao-Min Huang; Yi-Lung Yeh; Ting-Chien Chen (Environmental Science and Pollution Research, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Altered glucose metabolism and its association with carbonic anhydrase 8 in Machado-Joseph Disease - Guan-Yu Lin; Chung-Yung Ma; Li-Chung Kuo; Benjamin Y. Hsieh; Hanbing Wang; Chin-San Liu; Mingli Hsieh (Metabolic Brain Disease, 2022)

Biomechanical Analysis of Mandibular Implant-Assisted Removable Partial Denture with Distal Extension - Yung-Chung Chen; Chi-Lun Lin; Chen-Han Yu; Hung-Chih Chang; Yang-Ming Lin; Jia-Wei Lin (Journal of Medical and Biological Engineering, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Fine particulate matter measured by satellites predicts the risk of age-related macular degeneration in a longitudinal cohort study - Chung-Ling Liang; Chi-Min Wang; Chau-Ren Jung; Ya-Chu Chang; Chun-Ju Lin; Yu-Ting Lin; Bing-Fang Hwang (Environmental Science and Pollution Research, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Pusillimonas faecipullorum sp. nov., isolated from the poultry manure - Shih-Yao Lin; Asif Hameed; Chia-Fang Tsai; Yu-Shan Tang; Chiu-Chung Young (Archives of Microbiology, 2022)

Assessment of potential sediment disasters and resilience management of mountain roads using environmental indicators - Chao-Yuan Lin; Yuan-Chung Lai; Shao-Wei Wu; Fan-Chung Mo; Cheng-Yu Lin (Natural Hazards, 2022)
In recent years, extreme rainfall events occur frequently, causing serious watershed sediment disasters, destroying mountain roads, and endangering the safety of residents' lives and property. This study aims to deal with the spatial change of potential sediment movement on the road slope pre-disaster and to screen disaster hot spots for early warning and control system. The conceptual model is used to simulate the distribution of primary and/or derived disasters on a watershed scale to assess the impact of sediment disasters caused by heavy rain event. Correlation analysis shows that the models in assessment of primary disaster and derived disaster are significantly correlated with the collapse ratio and disaster ratio, respectively. Since the primary disaster has been considered when calculating the derived disaster risk, the terrain subdivision along Provincial Highway 21 (Tai-21) is extracted to understand the derived sediment disaster on the road slope. The model can effectively evaluate the road sections prone to disasters. According to the risk level, the hot spot of road slope disasters and the management of disaster resilience are determined and can be the reference for disaster prevention and control.

The brown root rot fungus Phellinus noxius affects microbial communities in different root‐associated niches of Ficus trees - Tse‐Yen Liu; Chao‐Han Chen; Yu‐Liang Yang; Isheng J. Tsai; Ying‐Ning Ho; Chia‐Lin Chung (Environmental Microbiology, 2022)
Summary Brown root rot (BRR) caused by Phellinus noxius is a destructive tree disease in tropical and subtropical areas. To understand how BRR affects the composition of the plant rhizoplane‐enriched microbiota, the microbiomes within five root‐associated compartments (i.e., bulk soil, old/young root rhizosphere soil, old/young root tissue) of Ficus trees naturally infected by P. noxius were investigated. The level of P. noxius infection was determined by quantitative PCR. Illumina sequencing of the internal transcribed spacer and 16S rRNA revealed that P. noxius infection caused a significant reduction in fungal diversity in the bulk soil, the old root rhizosphere soil, and the old root tissue. Interestingly, Cosmospora was the only fungal genus positively correlated with P. noxius . The abundance and composition of dominant bacterial taxa such as Actinomadura , Bacillus , Rhodoplanes , and Streptomyces differed between BRR‐diseased and healthy samples. Furthermore, 838 isolates belonging to 26 fungal and 35 bacterial genera were isolated and tested for interactions with P. noxius . Antagonistic activities were observed for isolates of Bacillus , Pseudomonas , Aspergillus , Penicillium , and Trichoderma . Cellophane overlay and cellulose/lignin utilization assays suggested that Cosmospora could tolerate the secretions of P. noxius and that the degradation of lignin by P. noxius may create suitable conditions for Cosmorpora growth.

Novel wing display and divergent agonistic behaviors of two incipient Psolodesmus damselflies - Leocris S. Batucan; Yu-Hsun Hsu; Jak W. Maliszewski; Liang-Jong Wang; Chung-Ping Lin (The Science of Nature, 2021)

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Three new species of Cylindrobasidium (Physalacriaceae, Agaricales) from East Asia - Yi-Chung Lin; Chia-Ling Wei; Chi-Yu Chen; Che-Chih Chen; Sheng-Hua Wu (Mycological Progress, 2021)

Image Segmentation in 3D Brachytherapy Using Convolutional LSTM - Jui-Hung Chang; Kai-Hsiang Lin; Ti-Hao Wang; Yu-Kai Zhou; Pau-Choo Chung (Journal of Medical and Biological Engineering, 2021)

Efficacy of Entomopathogenic fungus Aspergillus nomius against Dolichoderus thoracicus - Wei-Jiun Lin; Ming-Chung Chiu; Chung-Chi Lin; Yuan-Kai Chung; Jui-Yu Chou (BioControl, 2021)

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Computed Tomography Super-Resolution Using a Generative Adversarial Network in Bronchoscopy: A Clinical Feasibility Study - Heng-sheng Chao; Tsu-Hui Shiao; Chung-Wei Chou; Fang-Chi Lin; Yu-Te Wu; Der-Ming Liou (Journal of Medical and Biological Engineering, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Continental shelf morphology controlled by bottom currents, mud diapirism, and submarine slumping to the east of the Gaoping Canyon, off SW Taiwan - Yi-Ching Yeh; Chung-Lin Tsai; Shu-Kun Hsu; Hsiao-Shan Lin; Kuan-Ting Chen; Yen-Yu Cho; Chin-Wei Liang (Geo-Marine Letters, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Household airborne endotoxin associated with asthma and allergy in elementary school-age children: a case–control study in Kaohsiung, Taiwan - Yu-Chuan Yen; Chun-Yuh Yang; Tsu-Nai Wang; Pei-Chun Yen; Chi-Kung Ho; Kristina D. Mena; Tzu-Chi Lee; Kang-Shin Chen; Yuan-Chung Lin; Pei-Shih Chen (Environmental Science and Pollution Research, 2020)
To evaluate the association between the presence of asthma and allergy, and airborne endotoxin in homes of school-age children in Kaohsiung City, Taiwan, with a case–control study design by matching the age and class exposure. Data collection of home visits included an interviewer-administered questionnaire and air sampling of participants’ homes for endotoxin, bacteria, and fungi, as well as temperature and relative humidity measurements. Endotoxin was detected in all air samples with a median value of 0.67 EU m −3 . In the adjusted logistic regression model, household airborne endotoxin was associated with higher prevalence of asthma and allergy; OR = 4.88 (95% CI 1.16–20.55) for Q3 (between 0.67 and 1.97 EU m −3 ) vs. Q1 (< 0.31 EU m −3 ), with statistical significance. Airborne fungi were associated with higher prevalence of asthma and allergy; OR = 4.47 (95% CI 1.13–17.69) for Q3 (between 314 and 699 CFU m −3 ) vs. Q1 (< 159 CFU m −3 ) in adjusted logistic regression models. Airborne endotoxin and fungi were significantly associated with children’s asthma and allergy.

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

A full-scale study of external circulation sludge bed (ECSB) system for anaerobic wastewater treatment in a whiskey distillery - Yu-Chung Lin; Chen-Hua Ni; Chin-Yi Wu; Justin Chun-Te Lin (Environmental Science and Pollution Research, 2019)

Development of Multi-axis Motor Control Systems for Lower Limb Robotic Exoskeleton - Cheng-Tang Pan; Chun-Chieh Chang; Pei-Yuan Sun; Cheng-Lung Lee; Tzu-Chieh Lin; Chung-Kun Yen; Yu-Sheng Yang (Journal of Medical and Biological Engineering, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Mesorhizobium composti sp. nov., isolated from compost - Shih-Yao Lin; Asif Hameed; Yu-Ting Hsieh; Chiu-Chung Young (Antonie van Leeuwenhoek, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Herpes zoster and the risks of osteoporosis and fracture: a nationwide cohort study - Shu-Man Lin; Chih-Yung Wang; Ying-Yu Chen; Jen-Hung Wang; Chung-Chao Liang; Huei-Kai Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Detection, sequence analysis, and antibody prevalence of porcine deltacoronavirus in Taiwan - Tien-Huan Hsu; Hao-Ping Liu; Chieh-Yu Chin; Chinling Wang; Wan-Zhen Zhu; Bing-Lin Wu; Yu-Chung Chang (Archives of Virology, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Antiviral prophylaxis during chemotherapy or immunosuppressive drug therapy to prevent HBV reactivation in patients with resolved HBV infection: a systematic review and meta-analysis - Yi-Chia Su; Pei-Chin Lin; Hsien-Chung Yu; Chih-Chien Wu (European Journal of Clinical Pharmacology, 2018)

Acetaminophen Poisoning May Increase Coronary Artery Disease Risk: A Nationwide Cohort Study - Yu-Ting Chung; Che-Yi Chou; Wen-Chen Tsai; Wei-Kung Chen; Cheng-Li Lin; Wei-Sheng Chung (Cardiovascular Toxicology, 2018)

Levels and sources of heavy metals in soil, sediment, and food crop in the vicinity of electric arc furnace (EAF) steelmaking plant: a case study from Taiwan - Yuan-Chung Lin; Wen-Jhy Lee; Yu-Jen Shih; Syu-Ruei Jhang; Shih-Kai Chien (Journal of Soils and Sediments, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Arachidonic Acid Induces ARE/Nrf2-Dependent Heme Oxygenase-1 Transcription in Rat Brain Astrocytes - Chih-Chung Lin; Chien-Chung Yang; Yu-Wen Chen; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

The persistence and photostabilizing characteristics of benzotriazole and 5-methyl-1H-benzotriazole reduce the photochemical behavior of common photosensitizers and organic compounds in aqueous environments - Kenneth Hsien-Yung Chung; Yen-Ching Lin; Angela Yu-Chen Lin (Environmental Science and Pollution Research, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

IGF1R+ Dental Pulp Stem Cells Enhanced Neuroplasticity in Hypoxia-Ischemia Model - Hsiao-Yu Chiu; Chen-Huan Lin; Chung Y. Hsu; John Yu; Chia-Hung Hsieh; Woei-Cherng Shyu (Molecular Neurobiology, 2017)

Enhancing Immiscible Fluid Displacement in Porous Media by Capillary Pressure Discontinuities - C. A. Chung; Hung-Yu Lin (Transport in Porous Media, 2017)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

17β-Estradiol and/or estrogen receptor alpha blocks isoproterenol-induced calcium accumulation and hypertrophy via GSK3β/PP2A/NFAT3/ANP pathway - Peiying Pai; Bharath Kumar Velmurugan; Chia-Hua Kuo; Chung-Yi Yen; Tsung-Jung Ho; Yueh-Min Lin; Yu-Feng Chen; Chao-Hung Lai; Cecilia Hsuan Day; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2017)

Groundwater origins and recharge in a well field near Chien-Shih, Shinchu, Taiwan - Pei-Ying Lin; Louis Loung-Yie Tsai; Chung-Ho Wang; Kuei-Wen Chang; Yu-Yen Sheng; I-Tzu Chu; Wang-Ru Lee (Sustainable Water Resources Management, 2017)

IL-28 and IL-29 as protective markers in subject with dengue fever - Chih-Hsing Hung; Chung-Hao Huang; Lin Wang; Chun-Chi Huang; Meng-Chieh Wu; Yi-Ying Chin; Chun-Yu Lin; Ko Chang; Deng-Chyang Wu; Yen-Hsu Chen (Medical Microbiology and Immunology, 2017)

HCV core inhibits hepatocellular carcinoma cell replicative senescence through downregulating microRNA-138 expression - Tzu-Yue Shiu; Yu-Lueng Shih; An-Chieh Feng; Hsuan-Hwai Lin; Shih-Ming Huang; Tien-Yu Huang; Chung-Bao Hsieh; Wei-Kuo Chang; Tsai-Yuan Hsieh (Journal of Molecular Medicine, 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

The complete mitogenome of sea slug, Nembrotha kubaryana (Mollusca: Polyceridae) - Peng Xiang; Mao Lin; Yu Wang; Gilbert Audira; Sung-Tzu Liang; Chung-Der Hsiao (Conservation Genetics Resources, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

Dual‐compartmental transcriptomic + proteomic analysis of a marine endosymbiosis exposed to environmental change - Anderson B. Mayfield; Yu‐Bin Wang; Chii‐Shiarng Chen; Shu‐Hwa Chen; Chung‐Yen Lin (Molecular Ecology, 2016)
As significant anthropogenic pressures are putting undue stress on the world's oceans, there has been a concerted effort to understand how marine organisms respond to environmental change. Transcriptomic approaches, in particular, have been readily employed to document the m RNA ‐level response of a plethora of marine invertebrates exposed to an array of simulated stress scenarios, with the tacit and untested assumption being that the respective proteins show a corresponding trend. To better understand the degree of congruency between m RNA and protein expression in an endosymbiotic marine invertebrate, m RNA s and proteins were sequenced from the same samples of the common, Indo‐Pacific coral Seriatopora hystrix exposed to stable or upwelling‐simulating conditions for 1 week. Of the 167 proteins downregulated at variable temperature, only two were associated with m RNA s that were also differentially expressed between treatments. Of the 378 differentially expressed genes, none were associated with a differentially expressed protein. Collectively, these results highlight the inherent risk of inferring cellular behaviour based on m RNA expression data alone and challenge the current, m RNA ‐focused approach taken by most marine and many molecular biologists.

Identification of Vibrio parahaemolyticus in Seafood by Multiplex PCR - Chung-Saint Lin; Tser-Sheng Lin; Din-Yuan Yu; Yi-Cheng Su; Yung-Hsiang Tsai (Journal of Aquatic Food Product Technology, 2016)

Thrombin/Matrix Metalloproteinase-9-Dependent SK-N-SH Cell Migration is Mediated Through a PLC/PKC/MAPKs/NF-κB Cascade - Chien-Chung Yang; Chih-Chung Lin; Peter Tzu-Yu Chien; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2016)

CLEC5A is critical for dengue virus-induced osteoclast activation and bone homeostasis - Ya-Lang Huang; Szu-Ting Chen; Ren-Shyan Liu; Yen-Hsu Chen; Chun-Yu Lin; Chung-Hao Huang; Pei-Yun Shu; Ching-Len Liao; Shie-Liang Hsieh (Journal of Molecular Medicine, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Development of Home-Based Frailty Detection Device Using Wireless Sensor Networks - Chung-Chih Lin; Chun-Chang Chen; Pay-Shin Lin; Ren-Guey Lee; Jing-Siang Huang; Tsai-Hsuan Tsai; Yu-Chuan Chang (Journal of Medical and Biological Engineering, 2016)

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Roles of microRNA-1 in hypoxia-induced apoptotic insults to neuronal cells - Chia-Yu Chang; Tai-Ngar Lui; Jia-Wei Lin; Yi-Ling Lin; Chung-Hsi Hsing; Jhi-Joung Wang; Ruei-Ming Chen (Archives of Toxicology, 2016)

Parasite and Infected-Erythrocyte Image Segmentation in Stained Blood Smears - Yi-Wen Hung; Ching-Lin Wang; Chuin-Mu Wang; Yung-Kuan Chan; Lin-Yu Tseng; Chiu-Wen Lee; Kwong-Chung Tung (Journal of Medical and Biological Engineering, 2015)

Dysfunction Screening in Experimental Arteriovenous Grafts for Hemodialysis Using Fractional-Order Extractor and Color Relation Analysis - Ming-Jui Wu; Wei-Ling Chen; Chung-Dann Kan; Fan-Ming Yu; Su-Chin Wang; Hsiu-Hui Lin; Chia-Hung Lin (Cardiovascular Engineering and Technology, 2015)

Modeling and Analysis of the Viscoelastic Response of the Ankle Ligament Complex in Inversion Ankle Sprain - Che-Yu Lin; Yio-Wha Shau; Chung-Li Wang; Jiunn-Horng Kang (Annals of Biomedical Engineering, 2015)

Environmental stochasticity promotes copper bioaccumulation and bioenergetic response in tilapia - Wei-Yu Chen; Yun-Ru Ju; Chia-Jung Lin; Jeng-Wei Tsai; Szu-Cheih Chen; Chung-Min Liao (Stochastic Environmental Research and Risk Assessment, 2015)

IL-1β Induces MMP-9-Dependent Brain Astrocytic Migration via Transactivation of PDGF Receptor/NADPH Oxidase 2-Derived Reactive Oxygen Species Signals - Chuen-Mao Yang; Hsi-Lung Hsieh; Ping-Hsien Yu; Chih-Chung Lin; Shiau-Wen Liu (Molecular Neurobiology, 2015)

CO Induces Nrf2-Dependent Heme Oxygenase-1 Transcription by Cooperating with Sp1 and c-Jun in Rat Brain Astrocytes - Pei-Ling Chi; Chih-Chung Lin; Yu-Wen Chen; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2015)

Metabolites of Scutellariae Radix Inhibit Injury of Endothelial Cells in Hypoxia Device - Chia-Lun Chao; Shiuan-Pey Lin; Yu-Chi Hou; Pei-Dawn Lee Chao; Nen-Chung Chang; Yu-Ching Huang; Feng-Ming Ho (Journal of Medical and Biological Engineering, 2015)

Photodegradation of Alachlor Using BiVO4 Photocatalyst Under Visible Light Irradiation - Yi-Kuo Chang; Yu-Shen Wu; Chung-Shin Lu; Pei-Feng Lin; Tsung-Yen Wu (Water, Air, & Soil Pollution, 2015)

Genetic relationships and ecological divergence in Salix species and populations in Taiwan - Chun-Lin Huang; Chung-Te Chang; Bing-Hong Huang; Jeng-Der Chung; Jui-Hung Chen; Yu-Chung Chiang; Shih-Ying Hwang (Tree Genetics & Genomes, 2015)

Novel Link of Anti-apoptotic ATF3 with Pro-apoptotic CTMP in the Ischemic Brain - Chien-Yu Huang; Jin-Jer Chen; Jui-Sheng Wu; Hsin-Da Tsai; Heng Lin; Yu-Ting Yan; Chung Y. Hsu; Yuan-Soon Ho; Teng-Nan Lin (Molecular Neurobiology, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Permian ultrafelsic A-type granite from Besar Islands group, Johor, peninsular Malaysia - Azman A Ghani; Fatin Izzani Hazad; Azmiah Jamil; Quek Long Xiang; Wan Nur Atiqah Wan Ismail; Sun-Lin Chung; Yu-Ming Lai; Muhammad Hatta Roselee; Nur Islami; Kyaw Kyaw Nyein; Meor Hakif Amir Hassan; Mohd Farid Abu Bakar; et al. (Journal of Earth System Science, 2014)

Development, characterization and cross-species amplification of new microsatellite primers from an endemic species Cinnamomum kanehirae (Lauraceae) in Taiwan - Kuo-Hsiang Hung; Chia-Hung Lin; Huei-Chuan Shih; Yu-Chung Chiang; Li-Ping Ju (Conservation Genetics Resources, 2014)

Compartment‐specific transcriptomics in a reef‐building coral exposed to elevated temperatures - Anderson B. Mayfield; Yu‐Bin Wang; Chii‐Shiarng Chen; Chung‐Yen Lin; Shu‐Hwa Chen (Molecular Ecology, 2014)
Although rising ocean temperatures threaten scleractinian corals and the reefs they construct, certain reef corals can acclimate to elevated temperatures to which they are rarely exposed in situ . Specimens of the model Indo‐Pacific reef coral Pocillopora damicornis collected from upwelling reefs of Southern Taiwan were previously found to have survived a 36‐week exposure to 30°C, a temperature they encounter infrequently and one that can elicit the breakdown of the coral–dinoflagellate (genus S ymbiodinium ) endosymbiosis in many corals of the Pacific Ocean. To gain insight into the subcellular pathways utilized by both the coral hosts and their mutualistic Symbiodinium populations to acclimate to this temperature, mRNA s from both control (27°C) and high (30°C)‐temperature samples were sequenced on an Illumina platform and assembled into a 236 435‐contig transcriptome. These P. damicornis specimens were found to be ~60% anthozoan and 40% microbe ( S ymbiodinium , other eukaryotic microbes, and bacteria), from an mRNA ‐perspective. Furthermore, a significantly higher proportion of genes from the S ymbiodinium compartment were differentially expressed after two weeks of exposure. Specifically, at elevated temperatures, S ymbiodinium populations residing within the coral gastrodermal tissues were more likely to up‐regulate the expression of genes encoding proteins involved in metabolism than their coral hosts. Collectively, these transcriptome‐scale data suggest that the two members of this endosymbiosis have distinct strategies for acclimating to elevated temperatures that are expected to characterize many of Earth's coral reefs in the coming decades.

The role of Mss11 in Candida albicans biofilm formation - Pei-Wen Tsai; Yu-Ting Chen; Cheng-Yao Yang; Hsueh-Fen Chen; Te-Sheng Tan; Tzung-Wei Lin; Wen-Ping Hsieh; Chung-Yu Lan (Molecular Genetics and Genomics, 2014)

Two Frequent Mutations Associated with the Classic Form of Propionic Acidemia in Taiwan - Yen-Hui Chiu; Yu-Ning Liu; Wei-Ling Liao; Ying-Chen Chang; Shuan-Pei Lin; Chia-Chi Hsu; Pao-Chin Chiu; Dau-Ming Niu; Chung-Hsing Wang; Yu-Yuan Ke; Yin-Hsiu Chien; Kwang-Jen Hsiao; et al. (Biochemical Genetics, 2014)

Interface depth used in a two-layer model of nonlinear internal waves - Guan-Yu Chen; Chung-Lin Wu; Yu-Hwui Wang (Journal of Oceanography, 2014)

cDNA cloning and molecular characterization of five cellulose synthase A genes from Eucalyptus camaldulensis - Yen Lin; Yu-Ying Kao; Zenn-Zong Chen; Fang-Hua Chu; Jeng-Der Chung (Journal of Plant Biochemistry and Biotechnology, 2014)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Pemetrexed downregulates ERCC1 expression and enhances cytotoxicity effected by resveratrol in human nonsmall cell lung cancer cells - Ruey-Shyang Chen; Jen-Chung Ko; Hsien-Chun Chiu; Ting-Yu Wo; Yi-Jhen Huang; Sheng-Chieh Tseng; Huang-Jen Chen; Yu-Ching Huang; Yi-Jun Jian; Wei-Ting Lee; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Aerosol characteristics of different types of episode - Chung-Yih Kuo; Yan-Ruei Lin; Shih-Yu Chang; Chuan-Yao Lin; Chun-Hung Chou (Environmental Monitoring and Assessment, 2013)

Responses to booster hepatitis B vaccination are significantly correlated with genotypes of human leukocyte antigen (HLA)-DPB1 in neonatally vaccinated adolescents - Tzu-Wei Wu; Chen-Chung Chu; Tzu-Ying Ho; Huei-Wen Chang Liao; Sheng-Kai Lin; Marie Lin; Hans Hsienhong Lin; Li-Yu Wang (Human Genetics, 2013)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

Associations of T helper 1, 2, 17 and regulatory T lymphocytes with mortality in severe sepsis - Huang-Pin Wu; Kong Chung; Chun-Yao Lin; Bor-Yiing Jiang; Duen-Yau Chuang; Yu-Chih Liu (Inflammation Research, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Comparison of early transcriptome responses to copper and cadmium in rice roots - Chung-Yi Lin; Ngoc Nam Trinh; Shih-Feng Fu; Yu-Chyuan Hsiung; Li-Chiao Chia; Chung-Wen Lin; Hao-Jen Huang (Plant Molecular Biology, 2013)

Isolation and characterization of lactic acid bacteria from pobuzihi (fermented cummingcordia), a traditional fermented food in Taiwan - Yi-sheng Chen; Hui-chung Wu; Chiung-mei Wang; Chia-chun Lin; Yi-ting Chen; Yu-jyun Jhong; Fujitoshi Yanagida (Folia Microbiologica, 2013)

A molecular diagnosis method using real-time PCR for quantification and detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Ching-Chung Su; Chih-Ping Chao; Chi-Yu Chen; Chung-Jan Chang; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Coupled dynamics of energy budget and population growth of tilapia in response to pulsed waterborne copper - Wei-Yu Chen; Chia-Jung Lin; Yun-Ru Ju; Jeng-Wei Tsai; Chung-Min Liao (Ecotoxicology, 2012)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Cool seasons are related to poor prognosis in patients with infective endocarditis - Su-Jung Chen; Tze-Fan Chao; Yenn-Jiang Lin; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Tsui-Lieh Hsu; Wen-Chung Yu; Hsin-Bang Leu; Shih-Lin Chang; Shih-Ann Chen (International Journal of Biometeorology, 2012)

Novel ionic liquid supported-multicomponent reaction toward chimeric bis-heterocycles - Chih-Hau Chen; Chan-Yu Chen; Po-Tsung Lin; Chung-Ming Sun (Molecular Diversity, 2012)

A new phenylalkanoid from the rhizomes of Zingiber officinale - Soong-Yu Kuo; Rong-Jyh Lin; Yu-Ting Yeh; Jun-Yen Lee; Chung-Yi Chen (Natural Product Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Response to “Letter to editor re: Ling et al. 2011 (Environ Sci Pollut Res Int 18(6): 877–889)” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Elevated risk of hypertension induced by arsenic exposure in Taiwanese rural residents: possible effects of manganese superoxide dismutase (MnSOD) and 8-oxoguanine DNA glycosylase (OGG1) genes - Shiuan-Chih Chen; Chun-Chieh Chen; Chung-Yih Kuo; Chun-Huang Huang; Chin-Hsiu Lin; Zi-Yun Lu; Yi-Yu Chen; Hong-Shen Lee; Ruey-Hong Wong (Archives of Toxicology, 2012)

Response to “Dr. Luca Giannini’s Letter to the Editor” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Letter to Editor: Inappropriate exposure data and misleading calculations invalidate the estimates of health risk for airborne titanium dioxide and carbon black nanoparticle exposures in the workplace” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

A Review of the Major Penaeid Shrimp EST Studies and the Construction of a Shrimp Transcriptome Database Based on the ESTs from Four Penaeid Shrimp - Jiann-Horng Leu; Shu-Hwa Chen; Yu-Bin Wang; Yen-Chen Chen; Sheng-Yao Su; Chung-Yen Lin; Jan-Ming Ho; Chu-Fang Lo (Marine Biotechnology, 2011)

Assessing the potential exposure risk and control for airborne titanium dioxide and carbon black nanoparticles in the workplace - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2011)

Changes of Curdlan Biosynthesis and Nitrogenous Compounds Utilization Characterized in ntrC Mutant of Agrobacterium sp. ATCC 31749 - Li-Jun Yu; Jian-Rong Wu; Zhi-Yong Zheng; Xiao-Bei Zhan; Chi Chung Lin (Current Microbiology, 2011)

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning - Wei-Yu Chen; Yun-Ru Ju; Bo-Ching Chen; Jeng-Wei Tsai; Chia-Jung Lin; Chung-Min Liao (Ecotoxicology, 2011)

Population structure of Nouelia insignis (Asteraceae), an endangered species in southwestern China, based on chloroplast DNA sequences: recent demographic shrinking - Xun Gong; Shan-Shan Luan; Kuo-Hsiang Hung; Chi-Chuan Hwang; Chung-Jean Lin; Yu-Chung Chiang; Tzen-Yuh Chiang (Journal of Plant Research, 2011)

Phylogenetic position of a threatened stag beetle, Lucanus datunensis (Coleoptera: Lucanidae) in Taiwan and implications for conservation - Chung-Ping Lin; Jen-Pan Huang; Yat-Hung Lee; Ming-Yu Chen (Conservation Genetics, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

E4BP4 is a cardiac survival factor and essential for embryonic heart development - Yi-Jiun Weng; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Tung-Yuan Lai; Hsi-Hsien Hsu; Chang-Hai Tsai; Fuu-Jen Tsai; Ding-Yu Lin; James A. Lin; Chih-Yang Huang; Kwong-Chung Tung (Molecular and Cellular Biochemistry, 2010)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

A Non-fluorescent Derivative from Derivatizing trans, trans-Muconic Acid with 2-(2-Naphthoxy)ethyl-2-(piperidino)ethanesulfonate - Tang-Chia Chung; Wung-Pung Su; Hwang-Shang Kou; Yu-Ting Lin; Min-Yuan Hung; Hsin-Lung Wu (Journal of Fluorescence, 2010)

Empirical Models to Predict Parsimoniously the Mass and Number Concentrations of Ultrafine Particulate in Ambient Atmosphere - Chia-Pin Chio; Man-Ting Cheng; Yu-Chi Lin; Chung-Min Liao (Bulletin of Environmental Contamination and Toxicology, 2009)

Isolation and characterization of polymorphic microsatellite loci in Candidia barbata (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Yu-Min Ju; Lee-Shing Fang; Chung-Jian Lin (Conservation Genetics, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Complete sequence of a subgroup 3.4 strain of classical swine fever virus from Taiwan - Yu-Ju Lin; Maw-Sheng Chien; Ming-Chung Deng; Chin-Cheng Huang (Virus Genes, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Activation of Helicobacter pylori inorganic pyrophosphatase and the importance of Cys16 in thermostability, enzyme activation and quaternary structure - Mon-Juan Lee; Haimei Huang; Wei Lin; Ray-Rong Yang; Chien-Liang Liu; Chung-Yu Huang (Archives of Microbiology, 2007)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Contrasting phylogeographical patterns of two closely related species, Machilus thunbergii and Machilus kusanoi (Lauraceae), in Taiwan - Su‐Hwa Wu; Ching‐Yuan Hwang; Tsan‐Piao Lin; Jeng‐Der Chung; Yu‐Pin Cheng; Shih‐Ying Hwang (Journal of Biogeography, 2006)
Aim The purpose of this paper was to study the patterns of genetic variation, demographic history, haplotype relationships and potential location of diversity centres of two closely related species, Machilus thunbergii and Machilus kusanoi . Location The phylogeography of M. thunbergii and M. kusanoi was examined by sampling 110 and 106 individuals from 25 and 16 sampling sites, respectively, across their distributional range in Taiwan. Machilus thunbergii is distributed on the Asian mainland, South Korea, southern Japan, the Ryukyus, Taiwan and the Philippines, whereas M. kusanoi is endemic to Taiwan. These two species are closely related, and both are widely distributed in Taiwan but occupy different altitudinal zones and habitats. Methods The range‐wide variation of M. thunbergii and M. kusanoi in Taiwan was studied using chloroplast DNA (cpDNA) variations. A haplotype network was constructed with the computer program tcs . Nested clade analysis was conducted with the computer program ceodis , and various parameters of genetic diversity were calculated and neutrality tested by the computer program D na SP. Population differentiation was estimated using the programs arlequin and hapstep . The contribution of the populations to gene diversity and to allelic richness was calculated using the software contrib . The level of divergence for each population from the remaining populations was calculated as the mean value of pairwise F ST for each population against the rest of the populations. Results Extremely low levels of genetic differentiation were found for both species. This result suggested that these two species probably survived in multiple relict refugia with different population sizes throughout the island during low‐temperature periods of the Pleistocene. In addition, nested clade analysis (NCA) of cpDNA haplotypes indicated that restricted gene flow with isolation‐by‐distance characterized the recolonization after the Pleistocene by Tashueshan and Shiouhluan populations of M. thunbergii in the north‐central area west of the Central Mountain Range (CMR). In contrast, NCA analysis indicated that a major diversity centre on the southern tip of the island (Kending population) and contiguous range expansion characterized the recolonization by M. kusanoi of northern areas along the east side of the CMR. The major diversity centres found for the two species examined were further supported by the results of the mean F ST for individual populations in comparison with other populations, and of the contribution of the divergence component to the total diversity. Main conclusions This research supports the multiple relict refugia hypothesis for both species investigated. Populations of M. thunbergii at Shiouhluan and Tashueshan in the north‐central area west of the CMR represent a diversity centre currently expanding its size. A diversity centre at the southern‐edge population of M. kusanoi , and a contiguous range expansion from Kending, were found. These results indicate that the M. thunbergii populations at Tashueshan and Shiouhluan and the M. kusanoi population at Kending, and even Soukar, are evolutionarily significant units for conservation programmes.

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.